FACTORS AFFECTING STUDENT PERFORMANCE ON ENGINEERING DRAWINGS IN THE INDUSTRIAL REVOLUTION 4.0 - Azahar, Ridho; Putu Sudira (International Journal of Multidisciplinary Reseach, 2025)
The Industrial Revolution 4.0 has transformed education, particularly in technical drawing, requiring students to develop ICT literacy, social skills, and active engagement. However, many students face challenges in mastering ICT tools and collaborative skills, impacting their academic performance. This study uses a quantitative approach with an ex post facto design to analyze the relationships between student engagement, ICT literacy, social skills, and student performance. A Likert-scale questionnaire was distributed to 91 technical drawing students at Yogyakarta State University, and the data were analyzed using the SEM-PLS method. The results show that student engagement is the most influential factor in improving academic performance, followed by ICT literacy and social skills. Active student engagement enhances ICT literacy, which supports collaboration and boosts learning outcomes. Social skills, while less directly impactful, facilitate teamwork, which is crucial for technical drawing projects. This study emphasizes the need for integrated learning approaches combining engagement strategies, ICT literacy development, and social skill enhancement through digital tools and collaborative projects. These findings contribute to curriculum development, ensuring students are equipped to meet Industry 4.0 demands.